Examining requirement for formation of functional Presenilin proteins and their processing events in vivo. - Barakat, A.; Mercer, B.; Cooper, E.; Chung, H.M. (genesis, 2009)
Presenilin (Psn) is a multipass transmembrane protein that functions as the catalytic subunit of gamma-secretase for mediating intramembrane cleavage of type 1 transmembrane proteins. Normally active Psn is in the form of a heterodimer composed by its N-terminal and C-terminal fragments that are generated from a Presenilinase-mediated endoproteolytic cleavage within its large cytosolic loop during assembly of the protease complex. Using the Psn forms that either bypass or disable Presenilinase-mediated endoproteolysis, and a Psn form that has most of the large cytosolic loop deleted, we have established an in vivo system to enable investigations of Psn functional domains in Drosophila. We show that the Presenilinase-mediated endoproteolytic event is not essential for producing Psn activity during animal development, and is regulated by integrity of the large cytosolic loop of Psn in Drosophila. The Psn transgenic flies described here could be applied to a broad range of studies on Psn functioning and its related gamma-secretase activity at any developmental stage.